Impact of Human Capital Management Information System on Organization Performance: A Case of TRA Head Quarter in Dar Es Salaam - Arafa Mkongo; Lilian Joseph Macha (Research Trend in Technology and Management, 2023)
The study investigated three specific research objective namely to analyses the impact of e-recruitment on the quality performance of TRA Head Quarter; to examine the impact of e-training on customer satisfaction in service delivery system at TRA Head Quarter and to analyze the impact of e-communication system on timely operational performance of TRA Head Quarter. The study employed mixed research strategy based on qualitative and quantitative analysis to investigate human capital management information system on organization performance. The case study research design was used in analyzing the study. Data was collected through questionnaire and interview, and they were analyzed using qualitative and quantitative approaches. The study observed that e-recruitment system has impacts on increases rate of handling customer complaints hence ensures quality of services delivery and increase number of staff employed hence deliver quality works. The finding shows that e-training practices at the office added value of quick response to customer using online services hence impact to customer satisfactions and increases number of staff trained as the results increases professionalism in service delivery hence impacts on customer satisfactions with service delivery. The finding indicates that use of e-communication address operational challenges as the result contribute to operational performance, reduce time taken to respond to work activities that impact of operational performance and lower operational costs in work communication. The study recommends that policy development should be aligned with application of e-human capital management system that contributes toward improving operational performance of an organization.